Effect of earthworm and papain enzyme concentration on antioxidant activity of earthworm (Eudrilus eugeniae) protein hydrolysate - Salsabila, Dianah; Hidayat, Nur; Suprayogi, Suprayogi (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
The earthworm Eudrilus eugeniae (African Night Crawler) can be used as a raw material for making protein hydrolysates. Hydrolysis of earthworms using papain enzyme produces peptides that have bioactivity as antioxidants. Antioxidant activity in earthworm hydrolysate is caused by phenolic compounds that have an important role in neutralizing free radicals. This study aims to determine the effect of earthworm concentration and papain enzyme concentration on soluble protein, total phenolic content, and antioxidant activity. This study used the Randomized Block Design (RBD) method arranged with two factors, namely earthworm concentration (20% 30%, and 40% (w/v)) and papain enzyme concentration (8%, 10%, and 12% (w/v)) with three replications. Data analysis used Analysis of Variance (ANOVA) and continued with the DMRT test. The results showed that earthworm concentration, papain enzyme concentration, and the interaction between the two factors had a significant effect (p<0.05) on the test results of soluble protein, total phenolic content, and antioxidant activity. The treatment with earthworm concentration (40% (w/v)) and papain enzyme concentration (12% (w/v)) produced the highest mean soluble protein, total phenolic content, and antioxidant activity of 11.47%, 23.07 mg GAE/mL hydrolysate, and 3301.42 ppm.